2016
DOI: 10.1017/s0033291716002580
|View full text |Cite
|
Sign up to set email alerts
|

Predicting relapse after antidepressant withdrawal – a systematic review

Abstract: A substantial proportion of the burden of depression arises from its recurrent nature. The risk of relapse after antidepressant medication (ADM) discontinuation is high but not uniform. Predictors of individual relapse risk after antidepressant discontinuation could help to guide treatment and mitigate the long-term course of depression. We conducted a systematic literature search in PubMed to identify relapse predictors using the search terms ‘(depress* OR MDD*) AND (relapse* OR recurren*) AND (predict* OR ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 55 publications
(116 reference statements)
2
63
0
Order By: Relevance
“…In this study, we identified three post‐treatment predictors for long‐term depression severity: post‐treatment depression severity, negative beliefs about the future (hopelessness), and lower self‐esteem (self‐liking and self‐competence), all of which have been associated with an unfavorable course. Post‐treatment depression severity, or residual depression, has been found to have a strong prognostic value for an unfavorable course of depression (Berwian et al., ; Fava, Ruini, & Belaise, ; Hardeveld et al., ; Nierenberg et al., ; ten Doesschate, Bockting, Koeter, & Schene, ). Hopelessness as a predictor of long‐term depression severity is in line with the hopelessness theory of depression (Abramson, Metalsky, & Alloy, ; Liu, Kleiman, Nestor, & Cheek, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we identified three post‐treatment predictors for long‐term depression severity: post‐treatment depression severity, negative beliefs about the future (hopelessness), and lower self‐esteem (self‐liking and self‐competence), all of which have been associated with an unfavorable course. Post‐treatment depression severity, or residual depression, has been found to have a strong prognostic value for an unfavorable course of depression (Berwian et al., ; Fava, Ruini, & Belaise, ; Hardeveld et al., ; Nierenberg et al., ; ten Doesschate, Bockting, Koeter, & Schene, ). Hopelessness as a predictor of long‐term depression severity is in line with the hopelessness theory of depression (Abramson, Metalsky, & Alloy, ; Liu, Kleiman, Nestor, & Cheek, ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous research, we expected the number of previous episodes and childhood maltreatment to be identified as predictors as well (Berwian et al., ; Hardeveld et al., ; Kovacs et al., ; Nanni et al., ). However, our selection methods did not identify these variables.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These recommendations are based on evidence derived from the natural course of depression and overall relapse risk (Frank et al, 1991;Kessler et al, 2003;Nierenberg et al, 2010). However, the importance of these markers has been disputed (Berwian et al, 2017): two meta-analyses came to diametrically opposed conclusions about the relevance of the number of prior episodes (Viguera et al, 1998;Kaymaz et al, 2008), and five separate meta-analyses have failed to find an effect of length of ADM treatment on relapse risk after discontinuation (Viguera et al, 1998;Geddes et al, 2003;Kaymaz et al, 2008;Glue et al, 2010;Andrews et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients with major depressive disorder (MDD) have more than one major depressive episode, and at least 50% of patients who experience one episode are likely to experience another (APA, ; Kessler & Walters, ; Kessler, Zhao, Blazer, & Swartz, ). A higher number of previous episodes (Berwian, Walter, Seifritz, & Huys, ; Kendler, Thornton, & Gardner, ), more residual symptoms (Berwian et al., ; Nierenberg et al., ), and failure to reach remission after acute antidepressant treatment (APA, ; Rush et al., ) are associated with a greater risk of relapse, defined as the return of depression symptoms during an index episode. In addition, the STAR*D trial showed that the more acute treatment regimens a patient requires, the higher the risk of relapse (Rush et al., ).…”
Section: Introductionmentioning
confidence: 99%